Interactive verification of safety-critical software - Cruz, Daniela da (2013)
A central issue in program verification is the generation of verification conditions (VCs): proof obligations which, if successfully discharged, guarantee the correctness of a program vis-a`-vis a given specification. While the basic theory of program verification has been around since the 1960s, the late 1990s saw the advent of practical tools for the verification of realistic programs, and research in this area has been very active since then. Automated theorem provers have contributed decisively to these developments. This paper establishes a basis for the generation of verifi- cation conditions combining forward and backward reasoning, for programs consisting of mutually-recursive procedures an- notated with contracts and loop invariants. We introduce also a visual technique to verify a program, in an interactive way, using Verification Graphs (VG), where a VG is a Control Flow Graph (CFG) whose edges are labeled with contracts (pre- and postconditions). This technique intends to help a software engineer to find statements that are not valid with respect to the program’s specification.